Spectroscopic analyses combined with Gaussian and Coats-Redfern models to investigate the characteristics and pyrolysis kinetics of sugarcane residue-derived biochars. (10th November 2019) - Song, Fanhao; Wang, Xiaojie; Li, Tingting; Zhang, Jin; Bai, Yingchen; Xing, Baoshan; Giesy, John P.; Wu, Fengchang
Abstract: Biomass and biochars are considered good potential materials for environmental applications and their positive or negative effects on an ecosystem are mainly derived from the diverse physicochemical and pyrolytic kinetic properties. However, the characteristics of biomass resulted biochars have not been fully recognized. In this study, three biochars derived from dried sugarcane residue were prepared under 300, 500 and 700 °C. Spectroscopic techniques coupled with a Gaussian model were applied to innovatively de-convolute the existences and contributions of distinct overlapping peaks in the spectra, and then quantitatively evaluated the functional groups, sizes of aromatic clusters, and the degree of aromatic condensation of the sugarcane residue and biochars. Aromatic carbon/carbon-carbon double bond, single bonded oxygen, and pyrrolic nitrogen were dominant surface elements of the sugarcane residue and biochars. Decomposition and formation of different functional groups were quantitatively distinguished for pyrolysis temperature dependent biochars by Gaussian model. The changes of different carbon types and structures were attributed to the progressive dehydration, decarboxylation, aromatization reactions and structural formations of condensed carbon during the conversion of sugarcane residue into biochars. The biochars produced at higher pyrolysis temperatures exhibited higher fractions of bridgehead carbons, aromatic ring cluster sizes, and macromolecular aromatics. The sugarcane residue and biochars had fewer substituent groups at each aromatic ring and the biochars produced under 500 °C and 700 °C had an average of 14 more carbons in average aromatic cluster. The pyrolysis reactions of sugarcane residue and biochars were mainly associated with the degradation of hemicellulose, cellulose, and lignin components. The novel application of using spectroscopy coupled with a Gaussian model presented in this study has shown great potential as a valuable and effective characterization technique for studying the characteristics and pyrolysis kinetics of biochars. Results from this study benefit the greater understanding of the properties and reactivity of biomass and biochars, and their effects on pyrolysis optimization, carbon/pollutant sequestration, potential energy generation, and many other applications in the future. Graphical abstract: Image 1 Highlights: Overlapping Gaussian peaks for functional groups were de-convoluted and quantified. High temperature biochars exhibited more than 14 carbons in an aromatic cluster. Carbon condensation caused the changes of aromatic edge and bridgehead carbon ratio. Pyrolysis properties were related to hemicellulose, cellulose and lignin degradation.